MENINGKATKAN KEMAMPUAN BERKEMIH PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA PAGAR DEWA BENGKULU: MENINGKATKAN KEMAMPUAN BERKEMIH PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA PAGAR DEWA BENGKULU - Andri Kusuma Wijaya; Henni Febriawati; Ferasinta; Fatsiwi Nunik Andari (Gayaku Publisher, 2022)
Elderly is a continuation of a process in life which is marked by a process of decreasing the ability of body functions to adapt to stressful conditions due to the environment. The aging process is also a form of decline in the functions of the human body which is a comprehensive biological phenomenon characterized by the progressive evolution and maturation of organisms. One of the aging processes that occur in the elderly is a condition where the decreased ability to urinate (tub) that occurs in an elderly person, this condition is triggered by a decrease in the function of the work of the body's organs known as the urinary bladder or bladder that occurs due to malfunctioning muscle performance. sphincter to contract, resulting in a condition where the bladder becomes weak which can trigger an increase in the frequency of urination. The increased frequency of urination that occurs continuously can have an impact in the form of decreasing the quality of life of the elderly. This condition, if allowed to drag on continuously, will cause various problems, as for various problems such as health problems, social relations, and the economy. This condition certainly requires special attention to reduce the various impacts caused by the increased frequency of urination in the elderly by providing useful therapy or interventions. Various things can be done to improve the ability to urinate in the elderly such as health check-ups, conducting health education related to urinary incontinence and teaching or training the elderly to perform non-pharmacological interventions to improve voiding abilities such as Kegel exercises and deep breathing relaxation techniques for the elderly with complaints. increased frequency of urination at the Tresna Werdha Pagar Dewa Social Home in Bengkulu